36. EXPLORING STRESS AND EATING BEHAVIORS AMONG HEALTHCARE STUDENTS IN HO CHI MINH CITY (Vietnam Journal of Community Medicine, 2025)
Background: Healthcare students face a multitude of stress factors and eating disorders associated with the rigor and intensity of their training and education.Objective: The objective is to investigate the correlation between stress and eating behaviours among healthcare students at universities in Ho Chi Minh City.Method: Descriptive cross-sectional research was undertaken in Ho Chi Minh City, comprising 598 healthcare students using a convenient sample technique. Medical Student Stress Scale 22 (MSSS22) and the Eating Attitude Test 26 questionnaire (EAT26) were applied to assess stress and evaluate eating behavior, respectively.Results: Nearly half of the students were pharmacy (48%) and 238 were male (39.8%). Regarding body mass index (BMI), overweight and obese participants represented 74 (12.4%) and 11 (1.8%) respectively. Overall, participants with higher MSSS scored self-reported higher stress level and 11% (66) of them were at high risk of developing eating disorders. Statistical analysis revealed significant differences (p < 0.050) in average stress levels across groups classified by gender (p = 0.001), monthly income (p = 0.050), marital status (p = 0.015) and eating behavior (p < 0.001). In addition, a significant association (p = 0.011) was observed between eating behavior and students' academic majors.Conclusion: The study aims to investigate the relationship between stress levels and eating habits, thereby suggesting intervention strategies and counseling to enhance health as well as prevent eating disorders in the healthcare student community.
Keywords: Stress; eating behaviors; healthcare students; universities; Ho Chi Minh City.